2020
DOI: 10.1007/s11239-020-02326-x
|View full text |Cite
|
Sign up to set email alerts
|

Elderly people are inherently sensitive to the pharmacological activity of rivaroxaban: implications for DOAC prescribing

Abstract: According to both trial and clinical data on direct oral anticoagulants (DOACs) elderly patients are at greatest risk of bleeding. It is unclear whether age intrinsically affects anticoagulation response. To investigate the age-related sensitivity to DOACs, we compared the pharmacological activity of the direct factor Xa inhibitor, rivaroxaban, between young and elderly subjects ex-vivo. 36 fit elderly and 30 fit young subjects [median (IQR) age: 83(75–87) vs 30(26–38) years] provided a blood sample. Clotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The effect of age on CL/F was ≤30% and may not have significant clinical relevance as the drug label recommended by the FDA [ 45 ]. However, it should be noted that elderly patients in the real world have more concomitant diseases and are prone to have an unstable morbid state [ 51 ]. Besides the risk of increased PK exposure, elderly patients also have a higher risk of thrombotic and bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of age on CL/F was ≤30% and may not have significant clinical relevance as the drug label recommended by the FDA [ 45 ]. However, it should be noted that elderly patients in the real world have more concomitant diseases and are prone to have an unstable morbid state [ 51 ]. Besides the risk of increased PK exposure, elderly patients also have a higher risk of thrombotic and bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our study, this study focused on DRPs in general and not specific to DOAC therapy [ 29 ]. Other studies showed that elderly patients on DOACs for AF were at higher risk of bleeding compared with younger patients [ 30 ], had multiple comorbidities and higher mortality risk, and required drug therapy optimization to prevent poor outcomes [ 31 ]. Our study population was heterogenous, with patients on DOACs for multiple indications, and had wider age distribution, and hence, we did not find an association between age and comorbidities with DOAC-associated DRPs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that daily DOAC dose changes took place for a number of the patients in this cohort after the study was completed and these were decided independently of the present study findings. Apart from drug exposure, dose adjustment should also allow for elderly patients being inherently sensitive to DOACs as recent findings on rivaroxaban show 21 …”
Section: Discussionmentioning
confidence: 99%
“…Apart from drug exposure, dose adjustment should also allow for elderly patients being inherently sensitive to DOACs as recent findings on rivaroxaban show. 21 There are dose-response data available from phase III clinical trials of DOACs. A subanalysis of the RE-LY trial data by the manufacturer of dabigatran, Boehringer Ingelheim (Bracknell, Berkshire, UK), which included 9 183 patients (75% of patients in the RE-LY trial), with 112 ischaemic strokes/systemic emboli (1Á3%) and 323 major bleeds (3Á8%), showed that there were five-fold variations in plasma dabigatran concentration for each of the two doses (110 and 150 mg) that were tested.…”
Section: Discussionmentioning
confidence: 99%